Open Banking and Working Capital Efficiency: Evidence from API Adoption - Budianto, Hendy (SAFE-Network, 2025)
This study aims to examine the effect of Open Banking adoption through Application Programming Interfaces (APIs) on corporate working capital efficiency in Indonesia. Employing a quantitative explanatory approach, the research involved 90 respondents consisting of finance managers, accounting staff, and fintech decision-makers across multiple industrial sectors. Data were collected via an online survey using a five-point Likert scale and analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The findings reveal that API-based Open Banking adoption has a significant positive effect on working capital efficiency (β=0.482; p